Identifying useful project management practices: A mixed methodology approach - Fernandes, Gabriela; Ward, Stephen; Araújo, Madalena (International Journal of Information Systems and Project Management, 2022)
This paper describes a mixed methodological research approach for identifying practitioner perceptions of the most useful project management (PM) practices to improve project management performance. By identifying the perceived most useful tools and techniques, as having the most potential for increased contribution to project management performance, practitioners and organizations can select their priorities when improving PM practices. The research involved a programme of thirty interviews with Project Management professionals in Portugal, followed by a global survey. Completed questionnaires were received from 793 practitioners worldwide, covering 75 different countries. The results showed that the top twenty of the list of the most useful tools and techniques is composed of very well-known and widely used tools, such as: progress report; requirements analysis; progress meetings; risk identification; and project scope statement. PM practices in the top of list cover the overall PM life cycle from initiation to project closing, but particular relevance is given to tools and techniques from planning. The areas of knowledge, scope, time, risk, communication and integration, assume a high relevance, each with at least three PM practices on the top of the list.